1-Hydroxy-xanthine Inhibitors of Caf1 Deadenylase as a Potential Treatment for Osteoporosis - Ziemann, Max (2019)
Caf1 is a subunit of the CCR4-NOT complex. The role of Caf1 is that of a magnesium dependent deadenylase enzyme, which removes the poly(A) tail of mRNA (deadenylation). The degradation of the poly(A) tail has a downstream effect on mRNA translation and subsequent protein synthesis. Caf1 is implicated in several biological processes, an important one of which being the inhibition of osteoblasts. Osteoblasts are cells responsible for the formation of bone tissue and their inhibition leads to negative regulation of bone mass. Inhibition of Caf1 has been proposed as a potential pharmacological method of increasing osteoblast activity. This may serve as a novel approach to increasing bone density as a treatment for brittle bone diseases such as osteoporosis. 1-hydroxy-xanthines have previously been identified to act as inhibitors of Caf1 via the chelation of the magnesium ions present in the active site. This project aims to continue to develop novel 1-hydroxy xanthine compounds that act as Caf1 inhibitors by exploring the chemical space surrounding the compound’s substituents and the nature of their interaction with the Caf1 enzyme. This thesis reports the design, synthesis, chemical characterisation and pharmacological data of a library of novel compounds that act as Caf1 inhibitors using 3-(3-(dimethylamino)propyl)-1-hydroxy-7-phenethyl-3,7-dihydro-1H-purine-2,6-dione, 8j as a lead compound. 8j was selected as the lead because it was to the best of our knowledge, the most potent small molecule Caf1 inhibitor reported in the literature (IC50 = 3.30 µM). There exists a proposed binding mode for the interaction of 8j with Caf1 which was used to aid the design of new compounds as well as being assessed and re-examined in the context of new SAR findings. Derivatisation was explored around 3 substituents on the xanthine scaffold. A range of substituents and functional groups were tested at the 3- position. However, none showed improvement over the 3-substituent already present in 8j. A new synthetic pathway was developed to more easily derivatise the xanthine 7-position. Modification of substituents at the 7-position afforded several compounds (23k), (23o), (23p), and (23s) that were several times more potency than 8j. Specific substituents at the 3-position of benzene ring on the phenethyl fragment proved beneficial to potency. There was also found to be no strong relationship between the benzene ring electronics and the compounds binding, in disagreement with the proposed binding mode. These findings in combination with molecular modelling were used to revaluate the hypothesised binding mode and propose a new alterative. An additioal series of compounds were designed and synthesised with an additional functional group incorporated at the xanthine 8-position. This series gave rise to the compound with the highest potency towards Caf1 so far (35b) with a IC50 of 0.65 µM. Differential scanning fluorimetry was used to measure the binding of a diverse set of compounds to wild type Caf1 as well as variants containing substitutions of amino acids Phe43 and Tyr160. This was used to demonstrate the role of these residues in inhibitor binding. The residues were shown to be contributing towards the binding of certain compounds, in agreement with the newly proposed binding mode.